2021
DOI: 10.3390/agriengineering3030035
|View full text |Cite
|
Sign up to set email alerts
|

Tomato Leaf Diseases Classification Based on Leaf Images: A Comparison between Classical Machine Learning and Deep Learning Methods

Abstract: Tomato production can be greatly reduced due to various diseases, such as bacterial spot, early blight, and leaf mold. Rapid recognition and timely treatment of diseases can minimize tomato production loss. Nowadays, a large number of researchers (including different institutes, laboratories, and universities) have developed and examined various traditional machine learning (ML) and deep learning (DL) algorithms for plant disease classification. However, through pass survey analysis, we found that there are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(44 citation statements)
references
References 47 publications
0
20
0
2
Order By: Relevance
“…Xiang et al [32] established a lightweight convolutional neural network-based network model with channel shuffle operation and multiple-size modules that achieved accuracy levels of 90.6% and 97.9% on a plant disease severity and PlantVillage datasets, respectively. Tan et al [33] compared the recognition effects of deep learning networks and machine learning algorithms on tomato leaf diseases and found that the metrics of the tested deep learning networks are all better than those of the measured machine learning algorithms, with the ResNet34 network obtaining the best results. Alita et al [34] used the EfficientNet deep learning model to detect plant leaf disease, and it was superior to other state-of-the-art deep learning models in terms of accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Xiang et al [32] established a lightweight convolutional neural network-based network model with channel shuffle operation and multiple-size modules that achieved accuracy levels of 90.6% and 97.9% on a plant disease severity and PlantVillage datasets, respectively. Tan et al [33] compared the recognition effects of deep learning networks and machine learning algorithms on tomato leaf diseases and found that the metrics of the tested deep learning networks are all better than those of the measured machine learning algorithms, with the ResNet34 network obtaining the best results. Alita et al [34] used the EfficientNet deep learning model to detect plant leaf disease, and it was superior to other state-of-the-art deep learning models in terms of accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Many research works have been accomplished related to the TLDIs processing and analysis [1][2][3][4][5][6][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Some of the works are mentioned as follows.…”
Section: Related Workmentioning
confidence: 99%
“…The vegetables can be classified as tomato, potato, cabbage, cauliflower, broccoli, pumpkin, bean, etc. However, vegetable plant leaf diseases [1][2][3][4][5][6] and other diseases greatly hamper the production of vegetables. Tomato leaf diseases are focused in this work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bir başka disiplinler arası gerçekleştirilen çalışmada, yine PlantVillage domates veri kümesi ve domates hastalığı sınıflandırma problemi için en uygun ML/DL modellerinin belirlenmesi amaçlanmıştır [14]. Çalışmada, yerel ikili desen (LBP) ve GLCM yöntemleri kullanılarak 105 renk özelliği çıkarılmıştır.…”
Section: Giriş (Introduction)unclassified